2018
DOI: 10.18203/2394-6040.ijcmph20183089
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices regarding emergency contraception among married women in Ludhiana, Punjab, India

Abstract: Background: An unwanted and unintended pregnancy is a major concern in a women’s life as it has its adverse social and health outcomes. Emergency contraception (EC) is safe and effective method that gives women a second chance to prevent unwanted pregnancy after unprotected intercourse.Methods: This is a community based cross sectional study done in field practice area under the department of Community Medicine, Christian Medical College, Ludhiana, Punjab. A total of 400 respondents were selected by stratified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
1
4
0
3
Order By: Relevance
“…Contrary to study done among married women in Ludhiana, Panjab where 54.1% of respondents who have heard of EC had negative attitude towards ECPs, our result shows that majority of respondents (90%) who were aware of emergency contraceptive pills have positive attitude towards ECPs. 7 The result of this study correlate with the findings of a similar study conducted by Tesfaye et al and Verma et al that respondents have positive attitude towards ECPs in their respective studies. 19,22 In the present study, it is evident that 65% of respondents who are unaware of emergency contraceptive pills were less likely to utilize emergency contraceptive pills and out of 144 respondents, who were aware of ECPs, 63% has used it and majority of the nonusers revealed that they were using other contraceptive methods.…”
Section: Resultssupporting
confidence: 91%
“…Contrary to study done among married women in Ludhiana, Panjab where 54.1% of respondents who have heard of EC had negative attitude towards ECPs, our result shows that majority of respondents (90%) who were aware of emergency contraceptive pills have positive attitude towards ECPs. 7 The result of this study correlate with the findings of a similar study conducted by Tesfaye et al and Verma et al that respondents have positive attitude towards ECPs in their respective studies. 19,22 In the present study, it is evident that 65% of respondents who are unaware of emergency contraceptive pills were less likely to utilize emergency contraceptive pills and out of 144 respondents, who were aware of ECPs, 63% has used it and majority of the nonusers revealed that they were using other contraceptive methods.…”
Section: Resultssupporting
confidence: 91%
“…The ability of women to control their own fertility is absolutely fundamental to women's empowerment and equality. 4 Emergency Contraception (EC) is a safe and extremely effective method which was introduced three decades ago as a means to reduce the rates of unintended pregnancies, induced abortions, and unwanted childbirth. In spite of being introduced in the National Family Welfare Programme in 2003 and later declared as an Over-the-counter drugs, (OTC) product in 2005 it still remains a grossly underutilized option in the prevention of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Saini ve ark. (6) 2018'de Hindistan'da 400 evli kadın üzerinde yaptıkları çalışmada tüm katılımcılar içinde istenmeyen gebelik oranı %27,3 olarak bulunmuştur.…”
Section: Introductionunclassified
“…Öte yandan Hindistan'da yapılan bir çalışmada en sık ulaşılan AKY hakkındaki bilgi kaynağının %81,3 ile televizyon olduğu bulunmuştur. Çalışmayı yapanlar bu durumun sağlıkçıların AKY'a karşı tavırda olabileceklerine yorumlamıştır (6) . Çalışmamızda eğitim düzeyi 8 yıl ve altı olanlar bu terimi %40,6 oranıyla ASM'den duymuştur.…”
Section: Introductionunclassified
See 1 more Smart Citation